1990
DOI: 10.2337/diacare.13.8.836
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and NIDDM in Pima Indians

Abstract: The goal of this study was to determine the prevalence and incidence of periodontal disease and its relationship with non-insulin-dependent diabetes mellitus (NIDDM). Two thousand two hundred seventy-three Pima Indians (949 men, 1324 women) aged greater than or equal to 15 yr from the Gila River Indian Community in Arizona were examined between 1983 and 1989. Periodontal disease was diagnosed by tooth loss and by percentage of interproximal crestal alveolar bone loss ascertained from panoramic radiography. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
260
3
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(288 citation statements)
references
References 0 publications
11
260
3
14
Order By: Relevance
“…These assumptions may not be valid when the exposure and the covariates vary over time, because a covariate may be affected by the exposure and also be a confounder. In the present analysis, the level of hyperglycemia may be a confounder because it is a known risk factor for kidney disease (20) and is associated with periodontitis (3,4,6). On the other hand, the level of glycemia also rises as a consequence of periodontitis (6,7).…”
Section: Conclusion -P E R I O D O N T I T I Smentioning
confidence: 93%
See 2 more Smart Citations
“…These assumptions may not be valid when the exposure and the covariates vary over time, because a covariate may be affected by the exposure and also be a confounder. In the present analysis, the level of hyperglycemia may be a confounder because it is a known risk factor for kidney disease (20) and is associated with periodontitis (3,4,6). On the other hand, the level of glycemia also rises as a consequence of periodontitis (6,7).…”
Section: Conclusion -P E R I O D O N T I T I Smentioning
confidence: 93%
“…METHODS -Data were collected as part of a longitudinal study of diabetes and its complications in the Gila River Indian Community of Arizona (4). The diabetes study was initiated in 1965, and members of the community are invited to attend a research clinic for examination and screening every 2 years.…”
Section: Research Design Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by a study on Pima Indians which showed type 2 diabetes was associated with severity of periodontitis independent of gender. 9 Genco et al reported that BMI positively correlated with the severity of periodontal attachment loss and this relationship is modulated by insulin resistance. 19 In present study, cases had significantly higher BMI score as compared to controls which could be an aggravating factor for diabetes as well as periodontitis.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus is a complex disease with both metabolic and vascular components, and is characterized by hyperglycemia due to defects in insulin secretion or action or both. It is a systemic disease of the innate immune system 14) , and patients with DM are prone to severe periodontitis 11) , which is considered its sixth complication 8) . No significant differences were observed in the subgingival biofilm between periodontitis patients with or without DM 24) .…”
Section: Introductionmentioning
confidence: 99%